KINERJA PERAWAT DALAM MEMBERIKAN ASUHAN KEPERAWATAN BERPENGARUH TERHADAP KEPUASAN PASIEN RAWAT INAP - Khamida Khamida; Mastiah Mastiah (Jurnal Ilmiah Kesehatan, 2015)
The performance of nurses in providing nursing care is still considered unsatisfactory by the patient. The purpose of this study is to find out the relationship of the performance of nurses in providing nursing care with patient’s satisfaction in Multazam ward of Surabaya Islamic Hospital. Design of this studied Analytical survey. The population were all patients in Multazam ward of Surabaya Islamic Hospital with amount 85 person. Number of sample were 39 respondents, taken by simple random sampling. The independent variable is performance of nurses in providing nursing care, dependent variable is patient’s satisfaction. Instruments use questionnaires, data were processed by editing, coding, scoring, and tabulating, then analyzed by Chi-Square test with significant level α = 0.05. Study result showed most of respondents 39 (51.3%) the nurse had a poor performance, and most them (56,4%) the patients are not satisfied. Results of Chi-Square test analysis showed p (0.038) < α (0.05), so H0 is rejected means there is relationship of the performance of nurses in providing nursing care with patient’s satisfaction in Multazam ward of Surabaya Islamic Hospital. The conclusions of this study is the performance of nurses in providing nursing care influence to the patient satisfaction. Nurses should responsive to the complaints and expectations of patients due.